PENGARUH SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION MEMBER BPJS KESEHATAN DI WILAYAH JAWA TIMUR - Tanadi, Pratama (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
ABSTRACT The purpose of this study is to examine the effect of hospital service quality towards BPJS health service user satisfaction. Sample wes taken using simple random sampling to 50 patients and / or their families in 5 hospitals in East Java. Data was analyzed by Linear Regression. The result of the study shows that not all dimensions of service quality have a positive and significant impact on the satisfaction of BPJS health service users. Reliability, responsiveness, and empathy have a positive and significant influence on customer satisfaction. The limitation of this study is that it was carried out generally in hospitals collaborating with BPJS health service. However, this study does not assess customer satisfaction by the level (grade) of the hospital. Keywords: Service Quality, Customer Satisfaction, BPJS Health Service, Hospital Management